Formation mechanism of sealing edge pores for vacuum glazing using laser brazing technique. (January 2018) - Zhang, Jianfeng; Liu, Sixing; Zhang, Yanjun; Miao, Hong; Zhang, Shanwen; Zhang, Qi
Abstract: In view of the pore defect of vacuum glazing sealing layer, the research on side edge sealing of laser was made. The phase analysis of microstructure on sealing layer was investigated using scanning electron microscope (SEM) and energy spectrum analysis (EDS) to study the formation mechanism of sealing pores. The influence of laser power and welding rate on sealing edge porosity was researched. The results show that the sealing layer has evenly distributed bilayer structure of wetting layer with few pores caused by the residual gases between the solder particles (external) –melting layer with a large number of mutually disconnected isolated pores (inside). As the increase of laser power, the interface layer is compact and smooth and the pores decline in numbers. When the power exceeds a certain value, the interface becomes unsmooth with the increasing number of pores. The phenomenon of surface defects and blocky structures is generated with lower welding speed and greater energy output. On the other hand, the blocky structures, unmelted solders, pores and cracks are formed by the higher welding speed and smaller energy output. Therefore, the pore defect can be effectively avoided and reduced by the reasonable control of laser power and welding rate. Highlights: A new laser brazing sealing process for vacuum plate glass is proposed. The sealing edge pores characteristic of laser brazing joint is studied. The cause of formation and mechanism of sealing pores on welding joint is explored. Influence of different laser power level and welding rate to sealing pores is discussed.